STRATEGI PENGEMBANGAN SEKOLAH SWASTA MENGGUNAKAN PENDEKATAN BUSINESS MODEL CANVAS (BMC) DAN SWOT ANALYSIS PADA SDIT CAHAYA HATI KOTA BUKITTINGGI - Wijaya, Selvika; Lukito, Hendra (Komunitas Manajemen Kompetitif, 2024)
: The phenomenon of declining enrollment of prospective new students at the Cahaya Hati Integrated Islamic Elementary School (SDIT CH) in recent years indicates that the business model that has been built since the beginning is not qualified enough to compete with other schools in Bukittinggi City. This is considering the increasingly tight competition between educational institutions, especially at the elementary school level. For this reason, a new strategy is needed as well as the development of a new business model for SDIT CH. Through this research, it is necessary to know the external and internal factors that affect the school with a SWOT analysis so that it can find out the position of SDIT CH in formulating alternative strategies for the next and making it easier to develop a new business model. The method used in this study is a descriptive method with data collection techniques, namely interviews, observations and questionnaires both from internal and external schools. The analysis carried out was the analysis of the Internal Factor Evaluation (IFE) matrix, the External Factor Evaluation (EFE) matrix, the Internal External (IE) matrix, the Strengths-Weaknesses-Opportunities-Threats (SWOT) matrix and the Business Model Canvas (BMC). As a result of the SWOT analysis, SDIT CH's main strategy is the S-O strategy, which is to use strength to take advantage of opportunities. Regarding strategies that can be implemented, they include (1) maintaining student graduates so that they are always tested and have noble morals; (2) directing school achievements on academic and non-academic achievements at the national level; (3) strengthening the school's branding